Sculpting organ innervation - Barbara L. Hempstead (The Journal of Clinical Investigation, 2004)
Neurotrophic growth factors, including nerve growth factor (NGF) and glial-derived neurotrophic factor (GDNF), have well-established roles in promoting the innervation of target tissues, yet little is known about how the temporal and organ-specific expression of these factors is regulated. A new study reveals that NGF is a direct target of the well-characterized peptide factor endothelin-1 (ET-1), and that ET-1–induced NGF expression is required for sympathetic innervation of the developing heart. These results, and recent studies implicating GDNF and ET-3 in the patterning of the enteric nervous system, suggest that specific pairing of endothelins and neurotrophic factors may be used in distinct target organs to coordinate neuronal migration, differentiation, and survival.